2020
DOI: 10.1101/2020.05.17.20104604
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of Patients Who Return to Hospital Following Discharge from Hospitalization For COVID-19

Abstract: Background: Data on patients with coronavirus disease 2019 (COVID-19) who return to hospital after discharge are scarce. Characterization of these patients may inform post-hospitalization care. Methods and Findings: Retrospective cohort study of patients with confirmed SARS-CoV-2 discharged alive from five hospitals in New York City with index hospitalization between February 27th-April 12th, 2020, with follow-up of ≥14 days. Significance was defined as P<0.05 after multiplying P by 125 study-wide comparis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 12 publications
0
22
0
1
Order By: Relevance
“…By gender, men were 1.340 times more likely to be readmitted due to COVID-19 than women. Somani S et al found that out of 103 readmitted patients, 65 were men, two times more than women [5], and a study by Lina Marcela Parra Ramírez et al on COVID-19 readmitted patients showed that more men were readmitted due to COVID-19 [19]. Previous studies found differences in the effects of COVID-19 by gender.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…By gender, men were 1.340 times more likely to be readmitted due to COVID-19 than women. Somani S et al found that out of 103 readmitted patients, 65 were men, two times more than women [5], and a study by Lina Marcela Parra Ramírez et al on COVID-19 readmitted patients showed that more men were readmitted due to COVID-19 [19]. Previous studies found differences in the effects of COVID-19 by gender.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study in Spain by Lina Marcela Parra Ramírez et al reported that the duration of symptom onset and the length of stay was shorter in the readmitted patient group [19]. This may suggest improper patient care after discharge [5] or hasty discharge before complete recovery [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although efforts are underway to understand post-discharge outcomes in COVID-19 infected patients, to date they have been limited to case series ( 12 ), modest sample sizes ( 13 ), or single-center or geographically concentrated health systems ( 14 , 15 ). These extant studies may also be hampered by fixed inclusion/exclusion criteria ( 16 ).…”
mentioning
confidence: 99%